KEMAMPUAN GERAK DASAR LOKOMOTOR DAN MANIPULATIF SEBAGAI HASIL PEMBELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN DI SEKOLAH (Studi Pada Murid Kelas IV SDN 1 Ngoro Mojokerto) - Eko Lodang Januarisca, (Ordik, 2012)
Physical education, sportand healthas anintegral part ofeducation, has a unique functionthat is byusing the"movement" as a mediumforlearningstudents.One purpose ofthe subjectsof sports andphysical educationin elementaryschoolis so thatstudents canimproveskillsandbasicmovementskills. This study aims to assess to what extent the activities learning the sport an physical education in Ngoro 1 Mojokerto elementary school have been able to provide experience locomotor and manipulative movements to the boys and girl student. Besides it is also to find out whether the learning experience of motion in the from of motion capability locomotor and manipulative to the boys and girls at school is same or differents. The subject of this study are 32 elementary school pupils Ngoro 1 Mojokerto. Consistend of 16 male and 16 female student enrolled in the school year 2010-2011. Data obtained using a test motor ability of children of elementary school. From (1) shuttle run 4x10 meters: (2) throw the ball catching distance of 1 meter to the wall. Data were analyzed using statistical techniques. The result abtained as follow (1) there was an increase in basic locomotor movements skills ( p = 0,000 < a 0,05 or 10,1%). (2) there was an increase in basic manipulative movements skills ( p = 0,000 < a 0,05 or 14,72%). (3) there are differents in locomotor ability between men and woman student ( p = 0,001 < a 0,05). (4) there are differents in manipulative ability between men and woman student ( p = 0,003 < a 0,05). From the result of this study can be concluded that there is increasing movements to basic locomotor and manipulative as the learning outcomes of physical education in school. There are different in the ability of basic locomotor and manipulative motion between men and women student in elementary school Ngoro 1 Mojokerto